Community Land Ownership in the Perum Perhutani KPH East Banyumas Forest Area: A Juridical-Empirical Review Based on Pancasila Justice Principles - Sukirno, Sukirno; Setya, Kartika Winkar; Nurrozalina, Rakhma (Sean Institute, 2025)
State forest management in Indonesia faces a complex problem due to the existence of community-owned land within the state forest area, which often triggers tenurial conflicts. This study is conducted to analyze the legal status of community land ownership within state forests and assess dispute resolution based on the principles of Pancasila Justice. The research method adopted is a juridical-empirical approach, which is normative in terms of forestry and agrarian laws and regulations, and empirical through field observations and limited interviews conducted in the KPH East Banyumas. Research findings indicate that there were 0.9 hectares of community-owned land in Plot 14 of RPH Kaliputih, Forest Management Unit Section of Jatilawang, which has been factually controlled and cultivated for years with clear physical boundaries. Administratively, it still falls under a state forest area, as per the BATB. The dualism of regulations between the Forestry Law and the Basic Agrarian Law resulted in a lack of synchronization of interpretation and weak legal certainty. Through the Pancasila Justice Perspective, it is necessary for the settlement of disputes not only to be formally lawful but also to balance the rights of the state and the community, environmental sustainability, and social justice. An integrative resolution model is recommended through regulatory harmonization, verification of enclave land status, strengthening deliberation-based mediation mechanisms, and protection of the community rights based on the principle of substantive justice.